Industry Competitiveness and Jobs : An Evaluation of World Bank Group Industry-Specific Support to Promote Industry Competitiveness and its Implications for Jobs - Independent Evaluation Group (World Bank, Washington, DC, 2016)
This evaluation focuses on the World Bank Group’s support to enhancing industry-specific productivity and competitiveness, and examines the implications of improved industry competitiveness for employment during the last decade. The evaluation focuses on activities with explicit objectives to support competitiveness in the industries of manufacturing (including agribusiness), information and communication technology, tourism, and agriculture. The support to economy wide reforms, which in turn might also have an impact on these industries, is beyond the scope of this evaluation. The report draws conclusions on the relevance of the Bank Group’s support to productivity and competitiveness, the design and operational implementation of Bank Group strategies and performance results across different countries including the impact on employment generation.